Preparation method of flame-retardant and light-resistant core-shell water-based acrylic resin coating
By introducing DOPO and organic molybdenum compounds into acrylate resins, and using hydroxypropylprogyl ether and coumarin derivatives in the shell, the problems of melt droplet generation and poor light resistance of acrylate resin coatings are solved. It achieves higher flame retardancy and light resistance, and extends service life.
Patent Information
- Application Number
- CN202411288158.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-09-14
AI Technical Summary
Acrylate resin coatings produce melt droplets when they catch fire, causing the fire to expand, and their flame retardancy and light resistance are poor, limiting their application range.
9,10-dihydro-9-oxa-10-phosphophenophen-10-oxide (DOPO) and organic molybdenum compounds with smoke inhibition were introduced in the core layer of the acrylate resin, combined with the introduction of the shell layer Hydroxypropylprogyl ether and coumarin derivatives introduce these substances into the resin segment through free radical reactions, improving their flame retardancy and light resistance.
It significantly improves the flame retardancy and light resistance of acrylate resins, reduces the melt droplets and smoke generated by combustion, enhances its tolerance to ultraviolet rays, and extends its service life.
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a water-based acrylic resin coating, in particular to a method for preparing a flame-retardant and light-resistant core-shell water-based acrylic resin coating. Background Art
[0002] Polyacrylate is a type of polymer synthesized from acrylic acid or methacrylate as the main raw material. It has good mechanical properties, weather resistance and acid and alkali resistance. Its preparation process is simple and the cost is low. It is widely used as a film-forming material for leather finishing, architectural coatings and wood. However, due to the poor flame retardancy and light resistance of pure polyacrylate, its application range is limited. Therefore, its performance can be improved through chemical modification and structural design.
[0003] Zhang Chi et al. prepared an intumescent water-based fire retardant coating using ammonium polyphosphate as an acid source, pentaerythritol as a carbon source, dicyandiamide and diammonium hydrogen phosphate as gas sources, and thermosetting water-based epoxy emulsion and synthetic acrylic ester emulsion as film-forming materials. The fire resistance of the coating was studied by simulating large-plate combustion, and the composition of the intumescent carbon layer after burning was analyzed by Fourier transform infrared spectrometer (FTIR), and the carbon pores of the carbon layer were observed by electron microscopy. The results show that thermosetting water-based epoxy emulsion can effectively improve the fireproof and heat-insulating properties of intumescent vinegar-acrylic fire retardant coating. When the addition amount is 9wt%, the overall strength of the carbon layer reaches 3.22 N / cm after burning for 60 minutes. 2 The expansion ratio is 36 times, and the back-fire temperature of the wood board is only 61°C. The flame retardant is mixed with the acrylic emulsion by a compounding method. The method is simple, but the flame retardancy is poor by immersion absorption of the compound, and the light resistance of the acrylic resin is not involved.
[0004] The invention patent CN112409877A uses water, emulsifier, methacrylic acid and acrylic acid, heats to 45°C, stirs for 40 minutes, adds A monomer, and the emulsification time is 30-70 minutes; heats to 65°C and starts to reflux water, heats to 77°C and keeps warm, drips 0.3-0.7 parts by weight of initiator A, and the dripping time lasts for 1-3 hours, reacts for 2-4 hours, and obtains a core layer emulsion; simultaneously drips B monomer and 0.3-0.4 parts by weight of initiator A into the obtained core layer emulsion, and the dripping time lasts for 1- 2h, keep warm at 75-85℃ and stir to react for 3h, then add 0.6-1.1 parts by weight of flame retardant crosslinking agent, keep warm at 75-95℃ and react for 1-3h, cool to 50℃, add 0.3 parts by weight of emulsifier, react for 30min, add ammonia water to adjust the pH value to 7-8, and obtain flame retardant water-based core-shell acrylic resin coating and paint. The obtained flame retardant water-based core-shell acrylic resin coating and paint have good flame retardancy, and the obtained acrylic resin does not involve the key points of smoke and droplet core.
[0005] Invention patent CN110204989A adopts urea to replace traditional formaldehyde, modifies dimethyl phosphite and acrylamide, and coordinates with stabilizing materials for the preparation of core-shell acrylic resins. The amount of droplets generated by the combustion of the prepared acrylic resin is further reduced, and both smoke and droplets are reduced, showing a great improvement, but it does not involve the light resistance of acrylic resins.
[0006] Xu Weihuan and others sprayed plastic coatings on plastic surfaces and found that film-forming materials and titanium dioxide have a certain influence on the yellowing performance of plastic coatings. Coatings made from acrylic resins containing benzene rings have poor yellowing resistance and severe yellowing, while coatings made from 2310 titanium dioxide have good yellowing resistance and weaker yellowing. Ultraviolet absorbers can significantly improve the yellowing of plastic coatings. When the addition amount of ultraviolet absorbers is 0.3%, the yellowing resistance is the best and the yellowing color difference is the smallest. The ultraviolet absorber is combined with acrylic resins by physical mixing, but the ΔE exceeds 0.8, and the flame retardancy of acrylic resins is not involved, and the resulting acrylic acid is non-aqueous.
[0007] The invention patent application CN108624183A synthesizes a self-made emulsifier, which changes the traditional acrylic resin synthesis, which requires the addition of anionic and nonionic emulsifiers in the core-shell. p-aminobenzenesulfonamide is used as a catalyst for the emulsifier, tetramethylethylenediamine is used as a catalyst for the light-resistant material, and bromoacetyl can increase the light resistance to improve the light resistance of acrylic resin. However, the invention does not involve improving the flame retardancy of acrylic resin, and only studies the light resistance of acrylic resin within 450 minutes.
[0008] In summary, when the film of acrylic resin coating catches fire, molten droplets will be produced, causing a larger fire. At the same time, acrylic resin has poor flame retardancy, and the color change under light affects the service life of acrylic resin. Therefore, it is very necessary to study it. Summary of the invention
[0009] The present invention introduces carbon-forming 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and an organic molybdenum compound with good smoke suppression into the core layer of the acrylic resin, thereby achieving the triple effects of flame retardancy, droplet suppression and smoke suppression; at the same time, hydroxypropyl propargyl ether with bright reflection effect and light-absorbing coumarin derivatives are introduced into the shell layer, and the above substances are introduced into the acrylic resin chain segment by free radical reaction, so that the two act synergistically, the light resistance level and reflectivity of the acrylic monomer are improved, and thus the light resistance and flame retardancy of the acrylic resin are improved to a greater extent.
[0010] The preparation method of the flame-retardant and light-resistant core-shell water-based acrylic resin coating is prepared according to the following steps:
[0011] (1) Preparation of core layer emulsion: add 30-50g of water, 1.2-1.9g of emulsifier A, and 2.6-4.2g of methacrylic acid to a reaction container, mix and stir evenly, heat to 40-45°C, stir and react for 60min, add monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 1.1-2.2g of organic molybdenum compound, and emulsify for 20-30min; heat to 65°C, pass reflux water, heat to 80-90°C, dropwise add 0.4-0.7g of initiator, and continue the dropwise addition for 1-1.5h, and react at 70-90°C for 1-2h to obtain core layer emulsion;
[0012] (2) all monomers B and 0.2-0.4 g of initiator are added dropwise to the core layer emulsion obtained in step (1) for 1 h, and the mixture is stirred at 75-85°C for 1.5 h. 1.0-2.6 g of hydroxypropyl propargyl ether, 0.7-2.6 g of coumarin derivative and 0.02 g of glutaric acid are added, and the mixture is reacted at 60-70°C for 1 h. The mixture is cooled to 50°C, and 0.3 g of emulsifier B, 0.1 g of zirconium sulfate, 0.1-0.2 g of aluminum sulfate and 0.05 g of sodium maleate are added. The mixture is reacted for 30 min, and aqueous ammonia is added to adjust the pH to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating.
[0013] The monomer A is prepared by mixing 3-4g of ethyl acrylate, 4-5g of methyl methacrylate and 3-4g of hydroxyethyl acrylate;
[0014] The monomer B is prepared by mixing 2-6 g of ethyl acrylate, 4-8 g of methyl methacrylate and 3-6 g of hydroxyethyl acrylate.
[0015] The initiator is any one of ammonium persulfate, potassium persulfate and potassium hydrogen persulfate;
[0016] The preparation method of the organic molybdenum compound is:
[0017] (1) Add 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence, slowly heat to 70-85 °C, stir at 200 rpm for 16-24 h, remove the acetonitrile solvent in a vacuum evaporator, add 80-100 mL of ethyl acetate, filter to obtain a white solid, wash it with a small amount of ethyl acetate for 4-5 times, and dry it in a vacuum at 60-75 °C for 32-48 h to obtain intermediate A;
[0018] (2) Dissolve 0.11-0.12 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.10-0.13 mol of intermediate A alcohol solution while stirring, stir evenly, heat to 70-85 °C, reflux for 16-24 hours, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0019] (3) Dissolve 0.10 mol of intermediate B and 0.11 mol of oleic acid in 60-70 mL of dichloromethane solution, then add 40 mL of 1-2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution and stir to react for 10-12 h. The color of the product solution changes from dark blue to green. Take 30 mL of dichloromethane to extract the product, then wash the product with distilled water until no precipitation is generated in the silver nitrate solution. Dry the product to obtain an organic molybdenum compound.
[0020] The preparation method of coumarin derivatives is as follows:
[0021] Add 2.62 g of glycine methyl ester hydrochloride and 15-20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 12-24 h. During the reaction, an orange suspended substance appears in the bottle. Filter and wash to obtain an orange solid crude product, place it in a vacuum drying oven to dry, and use a DMF-H2O system for recrystallization to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0022] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid: water mixed in a volume ratio of 1:2) was added to the flask, and hydrolysis was carried out at room temperature for 30-60min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3. Then 3-4g of acryloyl chloride and 10-20mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 40-50°C for 1-2h, and then dried to obtain a coumarin derivative.
[0023] Emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1.
[0024] Emulsifier B is AEO-9.
[0025] The positive effects of the present invention are:
[0026] (1) The present invention utilizes the copolymerization reaction of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) PH bond, the double bond in the acrylic ester monomer, and the double bond of the organic molybdenum compound under the action of an initiator, introduces carbon-forming 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) into the acrylic ester resin chain segment, and introduces an organic molybdenum compound with good smoke suppression. Due to the increase in rigidity and carbonization of DOPO, the combustion continuity decreases and the melt is difficult to drip, and it is difficult to produce molten droplets, thereby avoiding secondary hazards, reducing the combustible gas released by combustion, and improving flame retardancy. At the same time, the organic molybdenum compound can also suppress the release of smoke, thereby achieving the triple effects of flame retardancy, molten drop suppression, and smoke suppression.
[0027] (2) The present invention selects 1-bromotetradecane to react with N-methyldiethanolamine to form a quaternary ammonium salt compound with a hydroxyl group, and then uses molybdenum acetylacetonate to react with the quaternary ammonium salt compound to introduce the molybdenum compound into the system, and then introduces oleic acid with a double bond into the molybdenum compound under an alkaline environment, and utilizes the double bond in the molybdenum compound to copolymerize with an acrylate monomer, and introduces the molybdenum compound into the acrylate resin segment to reduce the smoke generated by combustion;
[0028] (3) Using glycine methyl ester hydrochloride to react with salicylaldehyde to obtain 3-(2-(hydroxybenzylidene)amino) coumarin, and then using dilute hydrochloric acid to hydrolyze it to break the carbon-nitrogen double bond to form an amino group, so that the obtained coumarin derivative has an amino group, and reacts with the acyl chloride of acryloyl chloride to obtain a coumarin derivative with a double bond; the coumarin derivative is introduced into the acrylic ester monomer chain segment to improve the light resistance of the acrylic ester monomer. The principle of coumarin derivatives to improve the light resistance of materials is that the two coumarin groups in the coumarin derivatives will undergo a [2+2] cycloaddition reaction under ultraviolet light near 365nm to generate a dimer with a cyclobutane structure. The optical activity of the coumarin functional group is relatively high. Under the conditions of ultraviolet light of different wavelengths, it can undergo reversible photodimerization and photodepolymerization near 254nm. It consumes energy through continuous polymerization and depolymerization, reducing the effect on the light resistance of acrylic resins, and no catalyst is required in the entire reversible process;
[0029] (4) The present invention introduces hydroxypropyl propargyl ether with a bright reflective effect into the shell layer, and copolymerizes hydroxypropyl propargyl ether with acrylic ester monomers and introduces it into acrylic resin segments. The two cooperate with coumarin derivatives to improve the light resistance of acrylic ester monomers. Part of glutaric acid reacts with a small amount of hydroxyl groups of hydroxypropyl propargyl ether to introduce non-polar segments on hydroxypropyl propargyl ether, thereby increasing the surface smoothness of acrylic resin film. At the same time, zirconium sulfate and aluminum sulfate are introduced into the system. Aluminum sulfate and zirconium sulfate are hydrolyzed in water to form basic aluminum sulfate and basic zirconium sulfate. Basic aluminum sulfate or basic aluminum sulfate is complexed with the hydroxyl groups in the hydroxypropyl propargyl ether in the shell layer to effectively fix the hydroxypropyl propargyl ether, thereby improving the long-term light resistance of acrylic ester resin. Sodium maleate can inhibit the excessive hydrolysis of basic aluminum sulfate and basic zirconium sulfate and the violent reaction with hydroxypropyl propargyl ether. At the same time, zirconium sulfate can also improve the light resistance. DETAILED DESCRIPTION Embodiment 1
[0030] The preparation method of the flame-retardant and light-resistant core-shell water-based acrylic resin coating is prepared according to the following steps:
[0031] (1) Preparation of core layer emulsion: add 30g of water, 1.2g of emulsifier (sodium dodecylbenzene sulfonate and AEO-9 mixed in a weight ratio of 2:1), and 2.6g of methacrylic acid to a reaction container, mix and stir evenly, heat to 40°C, stir and react for 60min, add monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 1.1g of organic molybdenum compound, and emulsify for 20min; heat to 65°C, pass reflux water, heat to 80°C, drop 5.4g of ammonium persulfate solution dissolved in 5g of water, and continue dropping for 1h. React at 70°C for 1h to obtain core layer emulsion;
[0032] (2) all monomer B and 5.2 g of ammonium persulfate solution dissolved in 5 g of water are added dropwise to the core layer emulsion obtained in step (1) for 1 h, and the mixture is stirred at 75°C for 1.5 h. Then, 1.0 g of hydroxypropyl propargyl ether, 0.7 g of coumarin derivative and 0.02 g of glutaric acid are added, and the mixture is reacted at 60°C for 1 h. The mixture is cooled to 50°C, and 0.3 g of emulsifier (emulsifier AEO-9), 0.1 g of zirconium sulfate, 0.1 g of aluminum sulfate and 0.05 g of sodium maleate are added. The reaction time is 30 min, and aqueous ammonia is added to adjust the pH value to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating.
[0033] The monomer A is prepared by mixing 3g of ethyl acrylate, 4g of methyl methacrylate and 3g of hydroxyethyl acrylate;
[0034] The monomer B is prepared by mixing 2g of ethyl acrylate, 4g of methyl methacrylate and 3g of hydroxyethyl acrylate.
[0035] The preparation method of the organic molybdenum compound is:
[0036] (1) 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 70°C, and the reaction was stirred at 200 rpm for 16 h. The acetonitrile solvent was removed by vacuum evaporator, and 80 mL of ethyl acetate was added. A white solid was obtained after filtration, and washed with a small amount of ethyl acetate for 4 times, and vacuum dried at 60°C for 32 h to obtain intermediate A;
[0037] (2) Dissolve 0.11 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.10 mol of intermediate A in alcohol (add 30 mL of ethanol) solution while stirring, stir evenly, heat to 70 °C, reflux for 16 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0038] (3) Dissolve 0.10 mol of intermediate B and 0.11 mol of oleic acid in 60 mL of dichloromethane solution, then add 40 mL of 1 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution and stir to react for 10 h. The color of the product solution changes from dark blue to green. Take 30 mL of dichloromethane to extract the product, then wash the product with distilled water until no precipitation is generated in the silver nitrate solution. Dry the product to obtain an organic molybdenum compound.
[0039] The preparation method of coumarin derivatives is as follows:
[0040] Add 2.62 g of glycine methyl ester hydrochloride and 15 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction flask, and react at room temperature for 12 h. During the reaction, an orange suspended substance appears in the flask, and the orange solid crude product is obtained by filtration and washing, and is placed in a vacuum drying oven for drying, and is recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0041] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 30min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3, dried, and then 3g of acryloyl chloride and 10mL of toluene were added to the system, the pH was adjusted to 7.5, reacted at 40°C for 1h, and dried to obtain a coumarin derivative. Embodiment 2
[0042] The preparation method of the flame-retardant and light-resistant core-shell water-based acrylic resin coating is prepared according to the following steps:
[0043] (1) Preparation of core layer emulsion: add 50g of water, 1.9g of emulsifier prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1, and 4.2g of methacrylic acid into a reaction container, mix and stir evenly, heat to 45°C, stir and react for 60min, add monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO), and 2.2g of organic molybdenum compound, and emulsify for 30min; heat to 65°C and start to reflux water, heat to 90°C, drop 5.7g of potassium persulfate initiator solution dissolved in 5g of water, and continue to drop for 1.5h. React at 90°C for 2h to obtain core layer emulsion;
[0044] (2) To the entire core layer emulsion obtained in step (1), monomer B and 5.4 g of potassium persulfate initiator solution dissolved in 5 g of water were simultaneously added dropwise for 1 h, and the mixture was stirred at 85° C. for 1.5 h. Hydroxypropyl propargyl ether 2.6 g, coumarin derivative 2.6 g and 0.02 g of glutaric acid were added, and the mixture was reacted at 70° C. for 1 h. The mixture was cooled to 50° C., and 0.3 g of AEO-9, 0.1 g of zirconium sulfate, 0.2 g of aluminum sulfate and 0.05 g of sodium maleate were added. The reaction time was 30 min, and ammonia water was added to adjust the pH value to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating.
[0045] Wherein, the monomer A is a mixture of 4g of ethyl acrylate, 5g of methyl methacrylate and 4g of hydroxyethyl acrylate;
[0046] The monomer B is prepared by mixing 6 g of ethyl acrylate, 8 g of methyl methacrylate and 6 g of hydroxyethyl acrylate.
[0047] The preparation method of the organic molybdenum compound is as follows:
[0048] (1) Add 0.1 mol of 1-bromotetradecane, 0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent to a round-bottom flask in sequence, slowly heat to 85 °C, stir at 200 rpm for 24 h, remove the acetonitrile solvent in a vacuum evaporator, add 100 mL of ethyl acetate, filter to obtain a white solid, wash with a small amount of ethyl acetate 5 times, and vacuum dry at 75 °C for 48 h to obtain intermediate A;
[0049] (2) Dissolve 0.12 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.13 mol of intermediate A in alcohol (add 30 mL of ethanol) while stirring, stir evenly, heat to 85 °C, reflux for 24 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0050] (3) Dissolve 0.10 mol of intermediate B and 0.11 mol of oleic acid in 70 mL of dichloromethane solution, then add 40 mL of 2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution and stir to react for 12 h. The color of the product solution changes from dark blue to green. Take 30 mL of dichloromethane to extract the product, then wash the product with distilled water until no precipitation is generated in the silver nitrate solution. Dry the product to obtain an organic molybdenum compound.
[0051] The preparation method of coumarin derivatives is as follows:
[0052] Add 2.62 g of glycine methyl ester hydrochloride and 20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 24 h. During the reaction, an orange suspended substance appears in the bottle. Filter and wash to obtain an orange solid crude product, place it in a vacuum drying oven to dry, and use a DMF-H2O system for recrystallization to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0053] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 60min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3. Then 4g of acryloyl chloride and 20mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 50°C for 2h and dried to obtain a coumarin derivative. Embodiment 3
[0054] The preparation method of the flame-retardant and light-resistant core-shell water-based acrylic resin coating is prepared according to the following steps:
[0055] (1) Preparation of core layer emulsion: 40 g of water, 1.5 g of an emulsifier prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a mass ratio of 2:1, and 3.4 g of methacrylic acid were added to a reaction container, the mixture was stirred evenly, the temperature was raised to 45°C, the mixture was stirred and reacted for 60 min, monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) and 1.6 g of an organic molybdenum compound were added, and the emulsification time was 25 min; the temperature was raised to 65°C and refluxed water was started, the temperature was raised to 85°C, 5.55 g of a potassium persulfate solution dissolved in 5 g of water was added dropwise, the addition time was continued for 1.2 h, and the mixture was reacted at 80°C for 1.5 h to obtain a core layer emulsion;
[0056] (2) All monomers B and 5.3 g of potassium persulfate dissolved in 5 g of water are added dropwise to the core layer emulsion obtained in step (1) for 1 hour. The mixture is stirred and reacted at 80° C. for 1.5 hours. 1.8 g of hydroxypropyl propargyl ether, 1.65 g of coumarin derivative and 0.02 g of glutaric acid are added and reacted at 65° C. for 1 hour. The mixture is cooled to 50° C. and 0.3 g of AEO-9, 0.1 g of zirconium sulfate, 0.15 g of aluminum sulfate and 0.05 g of sodium maleate are added. The reaction time is 30 minutes. Ammonia water is added to adjust the pH value to 7-8 to obtain the flame-retardant and light-resistant core-shell water-based acrylic resin coating.
[0057] The monomer A is prepared by mixing 3.5 g of ethyl acrylate, 4.5 g of methyl methacrylate and 3.5 g of hydroxyethyl acrylate;
[0058] The monomer B is prepared by mixing 4 g of ethyl acrylate, 6 g of methyl methacrylate and 4.5 g of hydroxyethyl acrylate.
[0059] The preparation method of the organic molybdenum compound is as follows:
[0060] (1) 0.1 mol of 1-bromotetradecane, 0.11 mol of N-methyldiethanolamine and 100 mL of acetonitrile reagent were added to a round-bottom flask in sequence, the temperature was slowly raised to 75 °C, and the mixture was stirred at 200 rpm for 20 h. The acetonitrile solvent was removed in a vacuum evaporator, and 90 mL of ethyl acetate was added. A white solid was obtained after filtration and washed four times with a small amount of ethyl acetate. The solid was dried in a vacuum at 65 °C for 40 h to obtain intermediate A.
[0061] (2) Dissolve 0.11 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.115 mol of ethanol solution of intermediate A (add 30 mL of ethanol) while stirring, stir evenly, heat to 75 °C, reflux for 20 h, and remove the ethyl acetate solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B;
[0062] (3) Dissolve 0.10 mol of intermediate B and 0.11 mol of oleic acid in 65 mL of dichloromethane solution, then add 40 mL of 1.5 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution and stir to react for 11 h. The color of the product solution changes from dark blue to green. Take 30 mL of dichloromethane to extract the product, then wash the product with distilled water until no precipitation is generated in the silver nitrate solution. Dry the product to obtain an organic molybdenum compound.
[0063] The preparation method of coumarin derivatives is as follows:
[0064] Add 2.62 g of glycine methyl ester hydrochloride and 18 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 18 h. During the reaction, an orange suspended substance appears in the bottle. Filter and wash to obtain an orange solid crude product, dry it in a vacuum drying oven, and recrystallize it using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin;
[0065] The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid (concentrated hydrochloric acid and water were mixed in a volume ratio of 1:2) was added to the flask for hydrolysis at room temperature for 45min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3. Then 3.5g of acryloyl chloride and 15mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 45°C for 1.5h and dried to obtain a coumarin derivative.
[0066] The prepared acrylic resin coating was poured into a polytetrafluoroethylene mold with a thickness of 3 mm, and the droplet test, cone calorimetry, light resistance and other tests were carried out.
[0067] The following is a molten drop test:
[0068] (1) Sample preparation: Place the prepared acrylic resin film in a constant temperature and humidity chamber set at 23°C ± 0.5°C and 50% ± 5% humidity for 48 h. Then take it out and cut it into samples of 110 cm × 10 cm × 3 mm. Prepare 2 sets of samples, with 5 samples in each set.
[0069] (2) Parameter setting: Clamp about 5 mm from the top so that the sample is vertically downward. Place a rosin board at the bottom of the sample. Pad about 0.3 g of absorbent cotton on the board and place it evenly on the board. Adjust the gas flow rate to 105 ± 5 mL / min so that the flame height reaches 20 ± 1 mm. Set the combustion time to 10 s.
[0070] (3) Flame recording: After setting the parameters, start the flame ignition. After the 10s ignition, press the afterflame time start button. When the sample combustion is finished and only sparks are left, press the afterflame combustion end button and enter the afterburning time. When the flame is completely extinguished, press the afterburning time end button and record the burning afterflame time and afterburning time.
[0071] (4) Molten droplet observation: During the combustion process, pay attention to whether the combustion produces molten droplets, and whether the molten droplets dripping onto the cotton wool below will cause secondary combustion. Record the observation results.
[0072] Lightfastness is tested by keeping the distance between the sample and the light source at 25cm under a 300W ultraviolet lamp for 48 hours, observing the color change, and testing it on a HZ-3017 bulb-type yellowing resistance instrument. The lightfastness level is determined by comparing it with a colorimetric card.
[0073] Use JZ-300 universal colorimeter, and put the modified sample and blank into the bulb-type light source yellowing resistance test box at the same time. Keep the distance between the sample and the light source at 25cm under a 300W ultraviolet lamp, keep the temperature in the box at 60℃, and illuminate for 48 hours. Record the various values of the colorimeter to obtain the color difference value ΔE to describe the light resistance of acrylic resin. ΔE represents the degree of color change. The larger the ΔE, the more obvious the color change. Generally speaking, a ΔE value of 0~1.5 is a slight change; a ΔE value of 1.5~3 is a perceptible change; and a ΔE value of 3.0~6.0 is a significant change (see Wang Fang, Dang Gaochao, Wang Liqin, Photodegradation of Several Organic Cultural Relics Protection Polymer Coatings [J]. Journal of Northwest University, 2005, 35 (5): 56~58.)
[0074] Reflectivity determination method: Use a Gretag Macbeth Coloreye spectrophotometer (D65 light source, 10 degree observer, including UV) to measure the emission level of the resin from 360nm to 750nm, wherein the reflectivity at 660nm is defined as the maximum emissivity in this technical solution.
[0075] The ASTM E1354-1990 (2004 standard) was used to analyze and measure the sample using the Cone Calorimeter 2000 of the British FTT Company. The sample was 10cm×10cm, 3mm thick, and the thermal radiation power was 12kW / m 2 , determine the maximum heat release rate pkHHR kW / m 2 、THR total heat release MJ / m²、pSPR smoke generation rate reaches peak value m 2 / s and maximum total smoke release (TSR) m 2 / m 2 The fire performance index (FRI) is the ratio of the time to ignition (TTI) to the peak heat release rate (pHRR).2 kW -1 ) is the standard for measuring the flashover time at a fire scene. The larger the FRI value, the longer the flashover time and the longer the time it takes for people at the fire scene to escape.
[0076] Table 1 Properties of flame-retardant and light-resistant water-based core-shell acrylic resin films
[0077] index Embodiment 1 Embodiment 2 Embodiment 3 Comparative Example HkDJ 241.6 252.3 215.2 358.9 THR 36.8 35.7 34.2 80.3 pSPR smoke generation rate 0.12 0.14 0.16 0.46 TSR 120 135 141 258 FRI 0.113 0.124 0.118 0.356 Light fastness ΔE 1.3 1.4 1.5 3.8 Lightfastness grade 4.0 4.0 4.5 3.0 Reflectivity 98.8 98.9 99.1 92.5 Droplet situation No dripping No dripping No dripping Some molten droplets ;
[0078] The comparative example adopts Example 3 of CN112322132A. From the flame retardancy (pkHHR, THR, pSPR smoke generation rate, TSR, FRI and droplet situation) and light resistance index (light resistance ΔE, light resistance grade and emissivity) of the film formed by the flame retardant and light-resistant water-based core-shell acrylic resin in Table 1, it can be found that the light resistance changes slightly. The light resistance and flame retardancy of the present invention are better than those of the comparative example, indicating that the present invention significantly improves the light resistance of the core-shell acrylic resin.
[0079] Table 2 Performance of the film formed by flame retardant and light resistant water-based core-shell acrylic resin (flame retardant changes without adding some materials) Taking Example 3 as an example
[0080] index performance Some substances are not added THR 81.2 Without DOPO pSPR smoke generation rate 0.54 Without DOPO TSR 188 Without DOPO Droplet situation Produce a small amount of molten droplets Without DOPO THR 83.5 No organic molybdenum compound added pSPR smoke generation rate 0.99 No organic molybdenum compound added TSR 236 No organic molybdenum compound added Droplet situation Produces very small amount of molten droplets No organic molybdenum compound added THR 71.3 Add organic molybdenum compound, no acetylacetonate molybdenum powder pSPR smoke generation rate 0.68 Add organic molybdenum compound, no acetylacetonate molybdenum powder TSR 173 Add organic molybdenum compound, no acetylacetonate molybdenum powder Droplet situation Produces very small amount of molten droplets Add organic molybdenum compound, no acetylacetonate molybdenum powder THR 70.6 With organic molybdenum compound, without oil acid pSPR smoke generation rate 0.71 With organic molybdenum compound, without oil acid TSR 169 With organic molybdenum compound, without oil acid Droplet situation Produces very small amount of molten droplets With organic molybdenum compound, without oil acid ;
[0081] As can be seen from Table 2, the THR, pSPR smoke generation rate, TSR and droplet index of the polymer obtained without adding organic molybdenum compounds, oleic acid, acetylacetonate molybdenum powder and DOPO are all improved, showing the influence of the above substances on the flame retardancy of acrylic resin.
[0082] Table 3 Effect of light resistance of unadded materials (taking Example 3 as an example)
[0083] index performance Some substances are not added Light fastness ΔE 3.2 No coumarin derivatives added Lightfastness grade 3.0 No coumarin derivatives added Reflectivity 75.4 No coumarin derivatives added Light fastness ΔE 2.6 With coumarin derivatives, without salicylaldehyde Lightfastness grade 3.5 With coumarin derivatives, without salicylaldehyde Reflectivity 81.2 With coumarin derivatives, without salicylaldehyde Light fastness ΔE 2.7 No Hydroxypropyl Propargyl Ether Lightfastness grade 3.0 No Hydroxypropyl Propargyl Ether Reflectivity 61.3 No Hydroxypropyl Propargyl Ether Light fastness ΔE 1.9 No aluminum sulfate added Lightfastness grade 4.0 No aluminum sulfate added Reflectivity 98.2 No aluminum sulfate added Lightfastness grade 4.0 No glutaric acid added Reflectivity 94.2 No glutaric acid added ;
[0084] As can be seen from Table 3, the light resistance and glutaric acid indices decreased without the addition of coumarin derivatives, salicylaldehyde, hydroxypropyl propargyl ether, and aluminum sulfate, indicating the necessity of the above substances for light resistance.
[0085] The following is to examine the light resistance:
[0086] Lightfastness is determined by keeping the distance between the sample and the light source at 25 cm under a 300W ultraviolet lamp for 120 hours, observing the color change, and comparing with the color chart to determine the lightfastness level;
[0087] Use JZ-300 universal colorimeter, and put the modified sample and blank into the bulb-type light source yellowing resistance test box at the same time. Keep the distance between the sample and the light source at 25 cm under a 300W ultraviolet lamp, keep the temperature in the box at 60°C, and illuminate for 120 hours.
[0088] Table 4 Light fastness and durability
[0089] index Embodiment 3 No aluminum sulfate added No sodium maleate added No zirconium sulfate added Light fastness ΔE 2.2 3.1 2.8 3.3 Lightfastness grade 3.5 3.0 3.0 3.0 Reflectivity 97.6 95.2 96.8 94.5 ;
[0090] It can be found from Table 4 that the light resistance level under ultraviolet light irradiation is still high, and the emissivity is also high, while the light resistance without adding aluminum sulfate and zirconium sulfate decreases significantly, indicating that aluminum sulfate and zirconium sulfate play an obvious role in it, and the reaction is stable after adding glutaric acid and sodium maleate, which can promote the improvement of light resistance.
[0091] The acrylic resin film obtained by adding coumarin derivatives and hydroxypropyl propargyl ether does not turn yellow when exposed to light for 48 hours at a temperature of 60°C, while the acrylic resin film obtained without adding coumarin derivatives and hydroxypropyl propargyl ether appears light yellow.
Claims
1. A method for preparing a flame-retardant, light-resistant core-shell water-based acrylic resin coating, characterized in that: Prepare according to the following steps: (1) Preparation of core layer emulsion: add 30-50g of water, 1.2-1.9g of emulsifier A, and 2.6-4.2g of methacrylic acid to a reaction container, mix and stir evenly, heat to 40-45°C, stir and react for 60min, add monomer A and 0.01 mol of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 1.1-2.2g of organic molybdenum compound, emulsify for 20-30min; heat to 65°C, pass reflux water, heat to 80-90°C, dropwise add 0.4-0.7g of initiator, dropwise add for 1-1.5h, react at 70-90°C for 1-2h, and obtain core layer emulsion; (2) To the whole core layer emulsion obtained in step (1), all monomers B and 0.2-0.4 g of initiator are added dropwise at the same time for 1 h, and the mixture is stirred and reacted at 75-85° C. for 1.5 h. 1.0-2.6 g of hydroxypropyl propargyl ether, 0.7-2.6 g of coumarin derivative and 0.02 g of glutaric acid are added, and the mixture is reacted at 60-70° C. for 1 h. The mixture is cooled to 50° C., and 0.3 g of emulsifier B, 0.1 g of zirconium sulfate, 0.1-0.2 g of aluminum sulfate and 0.05 g of sodium maleate are added, and the reaction time is 30 min. Ammonia water is then added to adjust the pH value to 7-8, and the flame-retardant and light-resistant core-shell water-based acrylic resin coating is obtained. The monomer A is prepared by mixing 3-4g of ethyl acrylate, 4-5g of methyl methacrylate and 3-4g of hydroxyethyl acrylate; The monomer B is prepared by mixing 2-6 g of ethyl acrylate, 4-8 g of methyl methacrylate and 3-6 g of hydroxyethyl acrylate.
2. The method for preparing the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 1, characterized in that: The initiator is any one of ammonium persulfate, potassium persulfate and potassium hydrogen persulfate.
3. The method for preparing the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 1, characterized in that: The preparation method of the organic molybdenum compound is: (1) Add 0.1 mol of 1-bromotetradecane, 0.11-0.12 mol of N-methyldiethanolamine and 100 mL of acetonitrile to a round-bottom flask in sequence, slowly heat to 70-85 °C, stir at 200 rpm for 16-24 h, remove the acetonitrile solvent in a vacuum evaporator, add 80-100 mL of ethyl acetate, filter to obtain a white solid, wash with a small amount of ethyl acetate 4-5 times, and vacuum dry at 60-75 °C for 32-48 h to obtain intermediate A; (2) Dissolve 0.11-0.12 mol of molybdenum acetylacetonate powder in hot ethanol, slowly add 0.10-0.13 mol of ethanol solution of intermediate A while stirring, stir evenly, heat to 70-85 °C, reflux for 16-24 h, and remove the solvent by vacuum distillation to obtain a dark blue powder, namely intermediate B; (3) Dissolve 0.10 mol of intermediate B and 0.11 mol of oleic acid in 60-70 mL of dichloromethane solution, then add 40 mL of 1-2 mol / L sodium hydroxide aqueous solution dropwise to the mixed solution and stir to react for 10-12 h. The color of the product solution changes from dark blue to green. Take 30 mL of dichloromethane to extract the product, then wash the product with distilled water until no precipitation is generated in the silver nitrate solution. Dry the product to obtain an organic molybdenum compound.
4. The method for preparing the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 1, characterized in that: The preparation method of coumarin derivatives is as follows: Add 2.62 g of glycine methyl ester hydrochloride and 15-20 mL of deionized water to a round-bottom flask, adjust the pH to 8.5-9.0 with triethylamine, then add 5.51 g of salicylaldehyde to the reaction system, and react at room temperature for 12-24 h. During the reaction, an orange suspended substance appears in the bottle, which is filtered and washed to obtain an orange solid crude product, which is placed in a vacuum drying oven for drying and recrystallized using a DMF-H2O system to obtain 3-(2-(hydroxybenzylidene)amino)coumarin; The prepared 3-(2-(hydroxybenzylidene)amino)coumarin was transferred into a 250mL three-necked flask, and 100mL of dilute hydrochloric acid, which was a mixture of concentrated hydrochloric acid and water in a weight ratio of 1:2, was added to the flask, and hydrolysis was carried out at room temperature for 30-60min, and the pH was adjusted to 8-9. A large amount of brown suspended matter was precipitated in the flask. After the flask was cooled, it was filtered and washed to obtain a reddish-brown solid, which was recrystallized using EtOH:H2O in a volume ratio of 1:3, dried, and then 3-4g of acryloyl chloride and 10-20mL of toluene were added to the system, the pH was adjusted to 7.5, and the reaction was carried out at 40-50°C for 1-2h, and dried to obtain a coumarin derivative.
5. The method for preparing the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 1, characterized in that: The emulsifier A is prepared by mixing sodium dodecylbenzene sulfonate and AEO-9 in a weight ratio of 2:
1.
6. The method for preparing the flame-retardant, light-resistant core-shell water-based acrylic resin coating according to claim 1, characterized in that: The emulsifier B is AEO-9.
Citation Information
Cited By
Preparation method of flame-retardant, high-refraction and melt-drop-resistant acrylate resin coating
CN119875459A
Preparation Method of Flame-Retardant, High-Refractive-Index, Melting-Drip-Resistant Acrylate Resin Coating
CN119875459B
